A Clinical Study Resonance Frequency Analysis of Stability during the Healing Period - Muhamad Abu-Hussein; Chlorokostas Georges; Nezar Watted; Abdulgani Azzaldeen (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2016)
Implant stability plays a critical role for successful osseointegration, which has been viewed as a direct structural and functional connection existing between bone and the surface of a load-carrying implant. Achievement and maintenance of implant stability are prerequisites for successful clinical Outcome. Therefore, measuring the implant stability is an important method for evaluating the success of an implant. The aim of this clinical study was to measure the implant stability quotient using a method called resonance frequency analysis of dental implants during the healing period. Material and methods: A number of 43 patients received 152 Shark AL-Technology implant system either in the maxillary or in the mandibular arch. Implant stability was measured with an Osstell Mentor device (Osstel, AB, Sweden) using the resonance frequency analysis at the time of implant placement, 0, 2, 4, 8 and 12 weeks post insertion. Results: The mean implant stability quotient for all implants placed was 72,18. The lowest value of the implant stability quotient was at 2 weeks post insertion measuring 60,78. Conclusions: In relation to the gender the implants placed in female patients showed a higher mean value of the implant stability quotient. In relation to the location within the dental arch the implants placed in the anterior areas had a higher implant stability quotient than the ones places in the posterior areas of the arch.